2003
DOI: 10.1614/p2002-140
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mechanisms of reduced annual weed emergence in alfalfa

Abstract: Field experiments were carried out at the Facultad de Agronomía, Universidad de Buenos Aires, Argentina (34°25′S, 58°25′W), to evaluate the possibility of reducing weed seedling emergence through the use of alfalfa cultivars with low levels of winter dormancy and by increasing plant density from 200 to 400 plants m−2. It was hypothesized that these treatments would alter the temperature regime and the red (R)–far-red (FR) ratio of radiation to which seeds were exposed. Responses to management treatments were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Most of the weeds emerged in the first 50 DAP, which may explain why cover crop treatment did not affect weed emergence. Crop effects on weed emergence are more common in late-emerging weed species (Huarte and Arnold 2003). There were 72 and 70% fewer live weeds under the cover crops in February than January of yr 1 and 2, respectively (data not shown), indicating that most emerged weeds had senesced before the end of the cover crop season.…”
Section: Resultsmentioning
confidence: 98%
“…Most of the weeds emerged in the first 50 DAP, which may explain why cover crop treatment did not affect weed emergence. Crop effects on weed emergence are more common in late-emerging weed species (Huarte and Arnold 2003). There were 72 and 70% fewer live weeds under the cover crops in February than January of yr 1 and 2, respectively (data not shown), indicating that most emerged weeds had senesced before the end of the cover crop season.…”
Section: Resultsmentioning
confidence: 98%
“…In perennial crops, soil characteristics (organic matter, humidity, nutrients) and microclimatic conditions (temperature, light quantity and quality) relevant to weeds may be different to annual crops (Entz et al, 2002). Therefore, some weed species may not be able to germinate without soil disturbance (Huarte and Arnold, 2003), and a delayed nitrogen availability in legume-based cropping systems (in contrast to mineral N fertilisation) may favour species with larger seeds over smaller seeds (Liebman and Davis, 2000). Finally, the absence of soil tillage and the permanent vegetation cover may favour weed seed decay or seed predation by animals (Westerman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, [21] demonstrated negative impacts of climate variability on production in many crops, where the temperature variability increased the risks to yield, as shown via computer simulation and experimental studies. On the other hand, it has been reported that thermal oscillation may reduce both photosynthesis parameters and survival percentage, affecting the final performance of a determined crop [22]. Although both varieties decreased their performance in both field and greenhouse conditions when they were exposed to higher thermal amplitudes, they did so in different ways.…”
Section: Discussionmentioning
confidence: 95%